Hubungan Karakteristik Ibu dengan Perilaku Aborsi di Klinik PKBI Provinsi Jawa Timur - Rizka Fitria Nur Rohma (Universitas Airlangga, 2023)
Background: Abortion is one of the important issues that must be considered. This problem gets important attention in health problems because it affects the birth rate and maternal mortality. One of the factors that cause unsafe abortion is the lack of safe abortion services. Objective: To analyze the relationship between maternal characteristics and abortion behavior at PKBI clinics in East Java province. Methods: This type of research is analytic using a cross sectional design. Samples from 186 couples of childbearing age were taken randomly. Data collection used secondary data obtained from medical records of patients accessing abortion services at the PKBI clinic in East Java province. Data analysis used logistic regression. Results: The results showed the relationship between birth spacing (p = 0.001), mother's occupation (p = 0.00), contraceptive use (p = 0.00), history of miscarriage (p = 0.00), gestational age (p = 0.00), reasons for abortion (p = 0.00). = 0.00), family dependents (p = 0.004) with the behavior of couples of childbearing age who had an abortion, while maternal age (p = 0.273), parity (p = 0.341), maternal education (p = 0.069) did not have a relationship with the behavior of age couples fertile who had an abortion. Conclusion: birth spacing, mother's occupation, use of contraception, history of miscarriage, gestational age, reasons for abortion, and family responsibilities have a very large effect on abortion.